2013
DOI: 10.1007/s10646-013-1065-x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P4501A induction in primary cultures of embryonic European starling hepatocytes exposed to TCDD, PeCDF and TCDF

Abstract: Novel methods that predict the sensitivity of avian embryos to the toxic effects of dioxin-like compounds (DLCs) using either (1) knowledge of the identity of amino acids at key sites within the ligand binding domain of aryl hydrocarbon receptor 1 (AHR1) or (2) a luciferase reporter gene assay that measures AHR1 activation were recently reported. Results from both methods predict that European starling (Sturnus vulgaris) and domestic chicken (Gallus gallus domesticus) embryos have similar sensitivity to the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In the highest dose group that had starling chicks hatch (15.9 ng/g egg), induction of CYP1A4 mRNA expression was approximately 17-fold higher than for CYP1A5. These findings are consistent with results from an in vitro study using European starling hepatocytes exposed to dioxin-like compounds, in which the maximal response was significantly higher for CYP1A4 mRNA expression compared with CYP1A5 mRNA expression [20]. Similarly, in studies of other species using primary avian hepatocyte cultures exposed to dioxin-like compounds either in vitro or in ovo, typically significant differential expression is seen in type 1 species, with CYP1A4 Based on the amino acid sequence of the ligand-banding domain [16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the highest dose group that had starling chicks hatch (15.9 ng/g egg), induction of CYP1A4 mRNA expression was approximately 17-fold higher than for CYP1A5. These findings are consistent with results from an in vitro study using European starling hepatocytes exposed to dioxin-like compounds, in which the maximal response was significantly higher for CYP1A4 mRNA expression compared with CYP1A5 mRNA expression [20]. Similarly, in studies of other species using primary avian hepatocyte cultures exposed to dioxin-like compounds either in vitro or in ovo, typically significant differential expression is seen in type 1 species, with CYP1A4 Based on the amino acid sequence of the ligand-banding domain [16].…”
Section: Discussionsupporting
confidence: 91%
“…Results from an in vitro luciferase reporter gene assay support these predictions, as cells transfected with the European starling AhR1 ligand-binding domain were equally sensitive to AhR1 activation by dioxin-like compounds compared with cells with the full-length chicken AhR1 construct [19]. In addition, primary cultures of starling hepatocytes were as sensitive as chicken hepatocytes to induction of CYP1A4/5 after exposure to TCDD, although they were less sensitive than chicken hepatocytes to 2,3,4,7,8-pentachlorodibenzofuran and 2,3,7,8-tetrachlorodibenzofuran exposure [20].…”
Section: Introductionmentioning
confidence: 92%
“…Many studies showed that CYP activity can reflect the presence of environmental pollutants [ 29 ]. Alterations in CYP expression or enzymic activity in various organisms by many environmental contaminations have been reported; for example, heavy metals [ 30 , 31 ], 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) [ 32 , 33 ], and dexamethasone [ 34 ]. It was reported that Microcystis aeruginosa 7820 decreased the levels of cytochrome b5 and cytochrome P450 in mouse [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…European starlings are particularly useful as a study species because their ecology and physiology are well studied, they can be attracted to and reared in nest boxes, and they are amenable to captivity. Starlings have also been used widely in ecotoxicology studies and have recently been identified as a highly sensitive species given the structural affinity of their aryl hydrocarbon receptor to bind strongly to dioxin‐like compounds, including certain hydroxylated PCBs .…”
Section: Discussionmentioning
confidence: 99%